Implementation Of Islamic Monetary Policy In Indonesia's Economic System For The 2020-2024 Period - Ardiansyah, Jefri; Rahmawati, Lilik; Hasan, Hasan (ITB AAS INDONESIA Surakarta, 2024)
This study examines the implementation, potential, and challenges of Islamic monetary policy in Indonesia in supporting inclusive and sustainable economic growth. Despite Indonesia's status as the world's largest Muslim-majority country and its significant market potential for Islamic financial products, there are considerable gaps in the implementation of Islamic monetary policy. These gaps include low financial literacy, regulatory frameworks that are not yet fully supportive, and infrastructure limitations. The purpose of this research is to evaluate the implementation of Islamic monetary policy, analyze the challenges it faces, and provide strategic recommendations to enhance its effectiveness. The research methodology involves the analysis of secondary data from government reports and related institutions, as well as a literature review on Islamic monetary policy and best practices in other countries. The results of the study indicate that during the pandemic, instruments such as sukuk, IMA Certificates,